2022
DOI: 10.1021/acs.jafc.2c03464
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Interaction between Four Typical Carotenoids and Human Gut Microflora Using an in Vitro Fermentation Model

Abstract: Recent studies indicated a strong relationship between carotenoids and gut microflora. However, their structure− activity relationship remains unclear. This study evaluated the interaction between four typical carotenoids (β-carotene, lutein, lycopene, and astaxanthin) and gut microflora using an in vitro fermentation model. After 24 h of fermentation, the retention rates of the four carotenoids were 1.40, 1.38, 1.46, and 5.63 times lower than those of their without gut microflora control groups, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
5
10
3
Order By: Relevance
“…After the MNU treatment, the content of total SCFAs was significantly decreased by 45.32% compared with the CON group (Table 3). The content of SCFAs in the LUT group was 8.93% higher than that in the CON group, which was consistent with the results of Dai et al 22 The contents of acetic acid, propionic acid and n -butyric acid were significantly increased by 90.61%, 34.20%, and 155.15% after LUT treatment, respectively ( p < 0.05). Meanwhile, the content of total SCFAs in mice treated with EGCG was 29.95 ± 0.69 mmol g −1 , which was 8.63% higher than that in the MNU group.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…After the MNU treatment, the content of total SCFAs was significantly decreased by 45.32% compared with the CON group (Table 3). The content of SCFAs in the LUT group was 8.93% higher than that in the CON group, which was consistent with the results of Dai et al 22 The contents of acetic acid, propionic acid and n -butyric acid were significantly increased by 90.61%, 34.20%, and 155.15% after LUT treatment, respectively ( p < 0.05). Meanwhile, the content of total SCFAs in mice treated with EGCG was 29.95 ± 0.69 mmol g −1 , which was 8.63% higher than that in the MNU group.…”
Section: Resultssupporting
confidence: 90%
“…20,21 The latest report from our team using an in vitro fermentation model observed that LUT had a more significant impact on gut microflora than carotenes. 22 Similarly it has been found that EGCG treatment stimulated the growth of beneficial bacteria; meanwhile, it was degraded into a series of metabolites. 23 However, there is cur-rently no report on whether intake of LUT combined with EGCG can improve RP by regulating the gut microbiota.…”
Section: Introductionmentioning
confidence: 98%
“…Otherwise, in HFD-induced obese mice, dietary supplementation of 10 mg/kg LY significantly enhanced total cecal SCFAs concentrations ( 48 ). In an in vitro fermentation model, LY treatment also notably increased total SCFAs production of human gut flora ( 49 ). Collectively, we suppose the suppression of the NF-κB/NLRP3 inflammasome pathway in liver might be at least partially related to the modulation of intestinal microbiota and the microbial metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…In nature, the bioavailability of carotenoids is reduced [ 1 , 20 ] without processing or any type of treatment, leading to an accumulation in the colon [ 27 ], which is colonized by a large number of microorganisms [ 28 ] that play important roles in digestion and metabolism [ 29 ], as well as in maintaining normal gut physiology and health [ 30 ].…”
Section: Introductionmentioning
confidence: 99%